Characteristics and associated factors with mistreatment perception in medical interns in Peru - Vilchez Cornejo, Jennifer Steffany (2021)
Introduction: The medical internship is an entirely hospital stage where the mistreatment can adversely affect students' performance. The study's objective was to determine the characteristics and factors associated with the perception of abuse in medical interns in Peru. Materials and methods: Multicenter, cross-sectional and analytical study. We surveyed medical interns from eighteen Peruvian hospitals. Sociodemographic characteristics included a scale that mediates the perception of psychological, physical, and sexual mistreatment in the study. The researchers used generalized linear models and prevalence ratios at 95% confidence intervals. Results: 418 medical interns participated, 52.9% were women. The psychological, physical, and sexual mistreatment perceived was 91.9%, 55.5%, and 34%, respectively. A relationship was found in medical interns who perceived psychological maltreatment and performed rotated in surgery (RPa: 1.09; 95% CI: 1.00-1.20) came from a private university (RPa: 1.08; 95% CI: 1.02-1, 15) and being in a hospital of the Ministry of Health (RPa: 1.08; 95% CI: 1.01-1.16). Regarding physical abuse, they came from a private university (RPa: 0.77; 95% CI: 0.64-0.92) and were in a Ministry of Health hospital (RPa: 0.72; 95% CI: 0.55-0,94). The factors associated with sexual abuse were being a woman (RPa: 1.52; 95% CI: 1.15-2.01) and rotating in medicine (RPa: 1.52; 95% CI: 1.04-2.23). Conclusions: The abuse perceived by the inmates is high, being the psychological abuse the most frequent. The physical and psychological abuse was associated with the services' rotation, coming from a private university and interning in the Ministry of Health hospitals. Sexual abuse had associated with being a woman and rotation in the medical service.